Visualizing the Integrity of Chloroplast Envelope by Rhodamine and Nile Red Staining - An, Jinjie; Miao, Xin; Wang, Lulu; Li, Xu; Liu, Xiaomin; Gao, Hongbo (Frontiers in Plant Science, 2021)
Chloroplasts are essential organelles in plant cells with many important functions. Chloroplasts isolated by Percoll density gradient centrifugation are widely used in the study of chloroplasts. The intactness of isolated chloroplasts is necessary for many of the experiments. In the past, those isolated chloroplasts were either simply believed to be intact or had to be analyzed by indirect biochemical methods. Here we show a new method to check the intactness of isolated chloroplasts by staining their envelope with fluorescent dyes, Rhodamine or Nile red, and then observing them with a fluorescence microscope. With this method, broken chloroplasts and intact chloroplasts can be distinguished easily and their integrity can be checked in a few minutes. Results of this method agreed well with those of biochemical methods. Moreover, we have also found that sometimes the middle layer chloroplasts from the Percoll gradient centrifugation could be mostly broken, which could cause mistakes in the experiment. With our method, this problem can be easily found. This chloroplast envelope staining method can be used in the preparation of isolated chloroplasts to ensure the intactness.